Laboratório cinema e conservação: Conservação preventiva e gerenciamento da informação - Jussara Vitoria de Freitas (2008)
The search to identify, through physical analysis, the ideal process of treating the body of film of the School of Fine Arts, detect the factors that compromise the integrity of the work and prepare a proposal for preservation and packaging of the acquis to the development of a diagnostic from concepts of the science of conservation. The aim is also to assist in the practice of handling and conservation of these works through the structuring of the Laboratory of Cinema and Conservation of the acquis film. This, acondicionando entire collection in various media and formats to use academic and institutional. The study on risk management of the acquis was precursor to developing this proposal. It also implemented a database for collecting information cataloguing the work of an important substrate of the acquis film of the School of Fine Arts, Federal University of Minas Gerais composed of the funds Jose Tavares de Barros, Jose Américo Ribeiro and Evandro Lemos da Cunha.